Investigation of the temperature dependent impact behaviour of pin reinforced foam core sandwich structures. (15th October 2018) - Dimassi, M. Adli; John, Marianne; Herrmann, Axel S.
Abstract: Dry carbon and glass fibre bundles were inserted into a ROHACELL® 71HERO Polymethacrylimide (PMI) foam core under a specific inclination angle and pin pattern in order to improve the impact damage tolerance and the fracture toughness of foam core sandwich. Impact tests were performed on pin-reinforced foam core sandwich panels with different pin-configurations at impact energies between 35 J and 70 J. X-ray computed tomography and ultrasonic C-scan were used to determine the damages in the foam core. At room temperature no cracks were observed in the foam core. Using carbon fibre pins led to the creation of thermally induced cracks in the foam core after impacts at −55 °C, which is critical for the integrity of the structure. The modification of the manufacturing process parameters and the use of glass fibre pins are two solutions to improve the impact behaviour at −55 °C by delaying the thermal cracks to higher impact energies.